2009
DOI: 10.1038/oby.2009.8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Health in Women With Metabolic Syndrome: Clinical Aspects and Pathophysiology

Abstract: Although the classical cardiovascular risk factors (e.g., smoking and hypertension) are becoming more effectively managed, a continuous increase of the so-called "cardiometabolic risk" is noted. Starting from this century, the nomenclature "metabolic syndrome" has become more popular to identify a cluster of disorders including obesity, dyslipidemia, hypertension, and insulin resistance. It is a primary risk factor for diabetes and cardiovascular disease in both genders. Interestingly, the metabolic diseases d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
68
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 115 publications
(159 reference statements)
4
68
1
7
Order By: Relevance
“…It is well documented that premenopausal women are relatively safer from CVD as compared with men of the same age. 25 However, women's risk of CVD increases after menopause. 20 For instance, premenopausal women have a lower tendency to develop hypertension than do age-matched men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that premenopausal women are relatively safer from CVD as compared with men of the same age. 25 However, women's risk of CVD increases after menopause. 20 For instance, premenopausal women have a lower tendency to develop hypertension than do age-matched men.…”
Section: Discussionmentioning
confidence: 99%
“…Although in recent years gender differences in CVD risk have increasingly been recognized in the medical profession, usually clinical management of MetS is not tailored in a gender-specific manner. 25 Further research is needed to ascertain a better understanding of the pathophysiology underlying gender differences in MetS in order to identify gender-specific criteria for prevention, diagnosis and treatment of MetS in hypertensive patients. Given that the risk of metabolic aberrations is greater in hypertensive women than in hypertensive men at age 50, as was observed in our study, suggests that lifestyle interventions, known to be effective in reducing the clustering of risk in the MetS and potentially also treatment to reach recommended BP levels, should be more aggressive for women.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, a reduced incidence of type 2 diabetes mellitus and obesity was noted in otherwise healthy postmenopausal women who received estrogen. 3 This inverse correlation between estrogen and metabolic syndrome suggests that estrogen deficiency that accompanies menopause may play a role in the onset and development of metabolic syndrome. Thus, despite the controversies regarding ERT, it appears that younger postmenopausal women with metabolic syndrome may benefit from ERT.…”
mentioning
confidence: 99%
“…The pathophysiology of metabolic syndrome in perimenopausal and postmenopausal women is still not well understood, although ambient reproductive hormone levels are believed not to be the only variables that affect the frequency and severity of metabolic syndrome in women. It is particularly worrisome that some studies have indicated a potential tie between severity of menopausal syndrome (eg, hot flashes) and increased cardiovascular risk, 1,3 suggesting that younger postmenopausal women with metabolic syndrome who most need ERT for symptom relief may be at a greater risk of adverse effects from ERT.…”
mentioning
confidence: 99%
See 1 more Smart Citation